The Effectiveness of the Canva-Based CTL Model in Fiqh Learning in Improving the Learning Quality of Madrasah Tsanawiyah Students - Nisa', Khoirun; Wahyudi, Wahyudi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
The purpose of this study is to find out how effective the application of the CTL model and PPT-based Canva software is in improving the quality of learning in grade 7 Fiqh, with a sample of 50 students. The quantitative research used a two-group pretest-posttest design, data collected through the analysis of pretest and posttest results, from the experimental class that received the treatment and the control class did not receive the treatment, while the analysis method used Normality Test, Paired sample T-test and N-gain test to determine the effectiveness of the results of the Canva-based CTL learning model, thus the results that have been treated can be known for a more accurate comparison between those who have not been treated and those who have been treated. The learning results showed that both classes experienced an increase in understanding of fiqh material, but based on the N-gain test, the experimental class obtained an N-gain of 0.2884, while the control class obtained 0.0572. Based on the tests, it can be concluded that the ability of the experimental class is much better in understanding the fiqh material compared to the control class.